Evaluating the performance of means-tested benefits in Bulgaria - Iva Valentinova Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2012)
Little is known about the effectiveness of means-tested benefits in Bulgaria. Using individual and household level data, I analyse the performance of two social assistance and two means- tested child benefits. I find that the programmes reach a very small proportion of the households with incomes below a relative poverty line. Furthermore, the transfers are characterized with very high non-take up and inclusion of non-entitled or non-poor recipients. Poverty rates decrease by a small degree among benefit clients and yet, the impact is insufficient to affect overall poverty, or for the benefits to achieve their ultimate goals.
Keywords: D31; D61; D63; H55; I32; I38; 330; benefit non-take up; leakage; exclusion and inclusion errors; means-tested benefits; poverty; microsimulation